Pengolahan Pisang Sale untuk Penghasilan Alternative Masyarakat - Fikrihadi Kurnia; Maharsa Pradityatama; Syariful Wardana; Yusril Ilhamdani; Ridoni Saoloan Purba; Tegas Satriadi; Wahyudinil Islam; Zico Fatahillah Prastomo (LPMP Imperium, 2023)
Banana is one of the fruits widely consumed by the people of Indonesia. This can be proven by the many types of bananas that grow and are marketed in all regions in Indonesia. Banana sellers can quickly get bananas to market, and consumers can buy them at varying prices. However, the problem arising from banana fruit is its relatively short life span. It is characterized by black spots that appear on the banana and mark the banana will begin to rot. Therefore, the process of processing bananas into beru products, namely banana sales, is carried out. The service activity began with an interview with banana sellers at the Karang Jasi market and Sweta market, Mataram City. This resource person obtained information about the banana sale and how to process it. Banana sale processing is divided into three stages: banana preparation, skinning and slicing bananas, and drying. Banana drying takes ± eight days in consistently hot weather. Banana sale that is formed can be consumed directly and reprocessed into fried bananas. With this service activity, it is hoped that it can provide information to the community about how to process almost rotten bananas and use them as additional income.